Nuklearmedizin – Personalbelastung und Aktivitätsabgaben - Junker, D. (Nuklearmedizin - NuclearMedicine, 1991)
The Nuclear Medicine Division and 30 other groups at the University of Hannover School of Medicine are taken as examples to describe the diagnostic, therapeutic and research uses of radioactivity and the effectiveness of the associated radiation protection. The evolution of radiation exposures of 520 employees followed over the last six years and the methods used for the disposal of radioactive waste are explained. The adaptation of protective measures to individual and, in particular, specific working conditions has led to approximately 90% of all exposures remaining under the detection limit of the personal dosimeters during the entire observation period. Only a few people contributed to the collective radiation dose. In 1990, the average annual dose equivalent among personnel in the Nuclear Medicine Division was 0.12 mSv/person. By the installation of facilities for the storage of isotopes with short half-lives and of filters in the air circulation system, environmental contamination could be held much below the legal limits. Combustible and liquid waste containing radionuclides with long half-lives such as tritium and 14C had to be disposed of separately. However, they were a small fraction of the total radioactivity used.